Effectiveness of Different Pain Control Methods in Patients with Knee Osteoarthritis after Knee Arthroplasty. (19th June 2017) - Ming, Jin-Lain; Hung, Shiao-Pei; Huang, Hui-Mei; Tseng, Li-Hua; Huang, Chiung-Hui; Chen, I-Chun; Chen, Yu-Ping; Ting, Chien-Kun; Tung, Chen-Yin
Abstract : The number of patients with knee osteoarthritis has increased in tandem with population aging. Consequently, the number of knee arthroplasties has also risen. The postoperative pain is the biggest challenge faced by patients soon after knee arthroplasty; therefore, this study is among different methods for post-knee arthroplasty pain control. A prospective longitudinal research design was employed; 177 adult patients who proposed for primary knee arthroplasty were enrolled and recruited. The patients were divided into conventional Group 1 (n = 120 ) and patient-controlled analgesia (PCA) Group 2 (n = 57 ) according to the treatment methods they received. All patients experience the highest pain level on the day of their surgery; women complained of higher pain levels than men did, while the PCA group had lower postoperative pain. Meanwhile, patients with general anesthesia experienced more pain than those with spinal anesthesia in postoperative period. Patients with a higher postoperative pain index have a smaller optimal knee flexion angle. The PCA group had lower postoperative pain; all patients experienced the highest pain level on the day of their surgery. The results of this study could serve as a reference for nurses where PCA ensures a better postoperative pain control and therefore facilitates recovery and improves the quality of nursing.